"African management": concept, content and usability. Issue 3 (12th October 2015) - Seny Kan, Konan Anderson; Apitsa, Suzanne Marie; Adegbite, Emmanuel
Abstract : Purpose: – This paper aims to scrutinise the concept of "African Management" that increasingly fuels the debate on the management research of African organizations. Indeed, while management research in African context is all but invisible in management literature, the notion of "African management" emerges through a piecemeal corpus of literature that has arisen in response to the exclusion and marginalisation of Africa in the broad field of management literature. The idea underlying this reasoning is that the Western management model prevailing so far in Africa is inadequate because of cultural considerations. However, what is meant by "African management" still remains unfamiliar to both researchers and practitioners. Design/methodology/approach: – The authors conduct a selective review of the fragmented "African management" literature to identify directions it follows. This is carried out through an analytical framework aiming at investigating the usability of the "African management". Findings: – The paper identifies the key elements underlying the "African management" narrative. It also articulates these elements within a frame which represents an unprecedented attempt to render advocacy of "African management" more insightful. Originality/value: – The vibrant economic trends of Africa and its forthcoming dynamics are on the spotlight. At the same time, this upturn raises again a central concern about African societies' development in which organisations are expected to play a pivotal role. Yet the paucity and fragmented nature of the current state of "African management" research do not enable either practitioners or academics to get a deep understanding of African organisations. This article constitutes a major contribution by setting up a scheme of identifying convincingly the analytical parameters that really count in African organisations.